An investigation into the classroom talk of Iranian EFL novice vs. experienced teachers - Amir Ghajarieh; Nastaran Jalali; Mohammad Amin Mozaheb (UIN Salatiga, 2019)
This study investigates the classroom talk of Iranian EFL novice versus experienced teachers with emphasis on the quality of communicative features through a linguistic lens provided by the SETT (Self-Evaluation of Teacher Talk) framework and TTFS (Teacher Talk Functional Scale) checklist. In so doing, 10 intermediate-level classrooms running by five novice and five experienced teachers were observed, each case twice. Eight distinctive communicative features of TT emerged upon the initial analysis of database obtained from the audio-recordings of 20 class sessions, totaling 30 hours of naturally generated input. Subsequently, the audio-recorded materials were carefully transcribed and analyzed in correspondence with the observation data in an attempt to compare how novice and experienced teachers present their talk. The results indicated both novice and experienced teachers enact communicative aspects of classroom talk; however, the quality of presentation in the case of the experienced group was far better. This in turn highlights the importance of raising awareness regarding TT features in teacher training courses. New communicative aspects of teacher talk highlighted in this study, including the use of L1 and language gradation, would help define new research paths exploring the classroom discourse. Further research inspired by this study needs to explore other aspects of teacher-student interactions in various educational settings. Keywords: classroom talk, teacher talk, discourse, novice teachers, teacher education